2021
DOI: 10.1080/10408398.2021.1922873
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and delivery of bioactive citrus pomace polyphenols: a review

Abstract: Citrus pomace consists of the peel, pulp, and membrane tissues remaining after juice expression. Globally, around one million tons of citrus pomace are generated annually, which contains a variety of bioactive constituents that could be used as value-added functional ingredients in foods. However, the polyphenols in citrus pomace are not currently being utilized to their full potential, even though they can be used as nutraceuticals in functional foods and beverages. Citrus phenolics face significant roadblock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 84 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…The interactions between polyphenol and β‐cyclodextrin/protein/polysaccharide via microencapsulation and encapsulation can improve the stability, solubility, safety, bioavailability, biocompatibility, and bioactivity of polyphenols (Figure 6). The microencapsulation of polyphenols with β‐cyclodextrin significantly improves the processing stability and bioaccessibility of mulberry polyphenols (Li et al, 2020), olive pomace polyphenols (Radić et al, 2020), citrus pomace polyphenols (Caballero et al, 2021). Application of polyphenol‐ protein/polysaccharide interaction to fabrication, nanoparticles, emulsion, and encapsulation has been applied to improve the thermal stability and antioxidant activity of EGCG, resveratrol, quercetin, chlorogenic acid, and isoflavone.…”
Section: Technologies To Improve the Stability Of Polyphenolsmentioning
confidence: 99%
“…The interactions between polyphenol and β‐cyclodextrin/protein/polysaccharide via microencapsulation and encapsulation can improve the stability, solubility, safety, bioavailability, biocompatibility, and bioactivity of polyphenols (Figure 6). The microencapsulation of polyphenols with β‐cyclodextrin significantly improves the processing stability and bioaccessibility of mulberry polyphenols (Li et al, 2020), olive pomace polyphenols (Radić et al, 2020), citrus pomace polyphenols (Caballero et al, 2021). Application of polyphenol‐ protein/polysaccharide interaction to fabrication, nanoparticles, emulsion, and encapsulation has been applied to improve the thermal stability and antioxidant activity of EGCG, resveratrol, quercetin, chlorogenic acid, and isoflavone.…”
Section: Technologies To Improve the Stability Of Polyphenolsmentioning
confidence: 99%
“…16,[19][20][21] Of these studies, none used a plant protein. A more detailed review of existing research and opportunities in citrus pomace polyphenol encapsulation can be found in Caballero et al 22 The objective of this research was to assess the efficacy of a colloidal delivery system assembled from PPI and high methoxyl pectin (HMP) to encapsulate, protect, and deliver HT. Our specific objectives were to optimize the formation of stable PPI-HMP electrostatic complexes, determine the maximum concentration of HT that could be encapsulated within these complexes, and then to assess the impact of encapsulation on the dispersibility, antioxidant activity, and in vitro bioaccessibility of this polyphenol.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor determining the encapsulation of compounds inside alginate beads is their polarity. For more hydrophobic polyphenols, poor encapsulation occurs due to non-incorporation into the encapsulation mixture, which usually consists of hydrophilic materials, such as alginate or pectin, and thus their encapsulation remains a challenge [ 24 ].…”
Section: Resultsmentioning
confidence: 99%